Usage of Artificial Intelligence (AI) in Production Planning in Slovenia - Kerović, Jelisaveta (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
Artificial intelligence (AI) has become an integral part of advanced business practices. Within the framework of the Industry 4.0 initiative, it is intended for manufacturing systems to support production processes from planning to execution. This research aimed to investigate the state of AI integration in Slovenian companies, specifically in production planning processes. In the initial phase of the study, we analysed definitions of AI and production planning processes from professional literature, based on which we prepared a questionnaire. The research encompassed the state of AI presence in 2024 in 21 major manufacturing companies in Slovenia. Based on the results, we found that in year 2024, 24% of manufacturing companies already use AI. The main reasons for not using AI were identified as an internal lack of experts and the difficulty in recognizing the benefits for the company.